WAYS OF USING STEAM TECHNOLOGIES IN MODERN PRE-SCHOOL EDUCATIONAL ORGANIZATIONS - Abdumajitova , Sayohat Abdukasimovna (Educational Research in Universal Sciences, 2023)
introduction of STEAM educational technology into the field of preschool education, teaching as an elective subject not only to specialists working in the preschool education system, but also to students of higher education institutions studying in this field. Students studying in higher education institutions are learning using STEAM educational technology, changing their views on education. Educators, pedagogues, students and their parents (legal representatives) of preschool educational organizations can use STEAM technology based on the needs of education. The process and status of using STEAM technology in the world educational experience is analyzed.